HVAC design manual for hospitals and clinics. (ASHRAE, 2012)
"Provides in-depth design recommendations and proven, cost effective, and reliable solutions for health care HVAC design that provide low maintenance cost and high reliability based on best practices from consulting and hospital engineers with decades of experience in the design, construction, and operation of health care facilities"-- Provided by publisher.
Keywords: Hospital buildings -- United States -- Design and construction -- Handbooks, manuals, etc.; Clinics -- United States -- Design and construction -- Handbooks, manuals, etc.; Hospital buildings -- Heating and ventilation -- United States -- Handbooks, manuals, etc.; Clinics -- Heating and ventilation -- United States -- Handbooks, manuals, etc.; Hospital buildings -- Air conditioning -- United States -- Handbooks, manuals, etc.; Clinics -- Air conditioning -- United States -- Handbooks, manuals, etc.; elektronické knihy; electronic books